Do small shareholders count? - Kandel, Eugene; Massa, Massimo; Simonov, Andrei (Journal of Financial Economics, 2011)
We hypothesize that age similarity among small shareholders acts as an implicit coordinating device for their actions and, thus, could represent an indirect source of corporate governance in firms with dispersed ownership. We test this hypothesis on a sample of Swedish firms during the 1995–2000 period. Consistent with our hypothesis, we find that compared with shareholders of differing ages, same-age noncontrolling shareholders sell more aggressively following negative firm news; firms with more age-similar small shareholders are more profitable and command higher valuation; and an increase (decline) in a firm's small shareholder age similarity brings a significantly large increase (decline) in its stock price. The last effects are more pronounced in the absence of a controlling shareholder.